Autolyzed Yeast (Saccharomyces cerevisiae) Supplementation Improves Performance While Modulating the Intestinal Immune-System and Microbiology of Broiler Chickens - Bortoluzzi, Cristiano; Barbosa, José Guilherme Morchel; Pereira, Rafaela; Fagundes, Naiara Simarro; Rafael, Jaqueline Moreira; Menten, José Fernando Machado (Frontiers in Sustainable Food Systems, 2018)
The objective of this study was to evaluate the effects of dietary autolyzed yeast (AY; Saccharomyces cerevisiae) supplementation on growth performance, immune system, and intestinal bacterial count in broiler chickens. A total of 1,260 one-day-old male Ross AP95 chicks were placed in a completely randomized design (4 treatments, 7 replicates each, and 45 birds/replicate). The treatments were: basal diet – negative control (NC); basal diet supplemented with 55 ppm of zinc bacitracin – positive control (PC); NC + 0.2% of AY; NC + 0.4% of AY. The diets were formulated based on corn-soybean meal with 5% inclusion of wheat bran and 5% of poultry by-product meal. At 7 days of age, all birds were eye drop-vaccinated with live vaccine against coccidiosis. At 8 and 21 d of age, one chicken per pen was then euthanized by cervical dislocation to collect ileal and cecal contents for enumeration of Enterococcus sp., Escherichia coli and Lactobacillus sp. Yet, ileal samples were collected to analyze the gene expression of Claudin-1, IL-1β, IL-4, TLR-4 and MUC-2 through real time PCR. On d 21, it was observed that the inclusion of 0.2% of AY improved FCR (P < 0.05) when compared to the NC treatment. In the overall experimental period, the inclusion of zinc bacitracin and 0.4% of AY improved FCR (P < 0.05) compared to the NC group. On d 8, supplementation of 0.2 % of AY increased Enterococcus and both concentrations of AY reduced Lactobacillus in the ileal digesta compared to birds supplemented with zinc bacitracin. On d 21, 0.2% of AY reduced E. coli in the cecal digesta. On d 8, AY supplementation downregulated the expression of TLR-4 vs. the PC group (P = 0.04). On d 21, supplementation of AY upregulated the expression of IL-1β (P < 0.05) vs. the NC group. Supplementation of AY improved the growth performance of broiler chickens vaccinated against coccidiosis, partially explained by the modulation of the intestinal microbiota and immune-system.